Analysis Of Technical Efficiency Of Soybean Farming - Demak Riwardy Sitanggang; Edison Edison; Ardhiyan Saputra (Agribusiness Journal, 2024)
One of the most widely cultivated agricultural sub-sectors cultivated by farmers in Indonesia is the food crop sub-sector. Based on the topography of tidal swamp land, there are four types of land, namely Type A, B, C, and D. Type C land has the potential to be improved in its land use. One of the most widely cultivated food crop commodities in  Indonesia is soybean.  One way to cultivate soybeans is by optimizing the land, especially tidal land. Based on the topography of tidal swamp land, there are four types of land, namely Type A, B, C, and D. Type B land has the potential to be improved in its land use. Therefore, it is necessary to analyze the technical efficiency of farming in tidal marshland, especially in Type Bland. This research was conducted with the objectives of: Sub-district, East Tanjung Jabung Regency, 2) Analyzing the level of technical efficiency of soybean farming in Rantau Rasau sub-district, East Tanjung Jabung Regency, 3) Analyzing the influence of age, education, experience, number of family members and extension workers on the technical inefficiency of soybean farming in Rantau Rasau sub- district, East Tanjung Jabung Regency. The analytical tool used is the analysis of the Stochastic Frontier production function with Cobb-Douglass and calculates the level of efficiency and inefficiency.  This research was conducted in the Rantau Rasau sub-district,  East  Tanjung  Jabung  Regency.  The sampling technique was the census method with a sample of 42 farmers. The data used were secondary and primary.  The results showed that: 1) The condition of the land in the study area is tidal land with an average production of 1,039 Kg. 2) The use of production inputs in the study area was technically efficient reaching 0.751. 3) Simultaneously and partially age, education, experience, number of family members and counselling have no significant effect on production.